An Analysis of Reading Performances of Indonesian EFL Learners for Extensive Reading Practice - Syofia Delfi; Hamidah Yamat (Journal of Educational Sciences, 2017)
Learners’ reading performances are needed to be studied in order to clarify the appropriate context of studies about learners’ extensive reading experiences. This article is based on a preliminary study on “a Case Study on Two Indonesian Learners’ Extensive Reading in English Experiences towards Developing Reading Competency”. This article aimed to answer two questions: (1) How is The Indonesian EFL learners’ reading performance before learning extensive reading? (2) How is The Indonesian EFL learners’ reading TOEFL score for reading section before learning extensive reading? An analysis was conducted for the data on the documents of reading performance and Reading Section of TOEFL score. The result of this study found: (1) The Indonesian EFL learners’ reading performance before learning extensive reading is in the range 66-80 (B) in Reading III for all learners (100%) (2) The Indonesian EFL learners’ TOEFL score for Reading section before learning extensive reading is in the range 51% - 80 %. These preliminary data were needed in order to indentify the learners’ reading performances, therefore, it is expected that the findings are meaningful for the study designed.